(untitled) (Global Journal of Human-Social Science, 2024)
The paper examined entrepreneurial intentions within the higher educational institutions in Nigeria it also assessed the benefits of entrepreneurship in higher educational institutions and socio-economic development in Nigeria Primary and secondary data were used Primary data were collected through questionnaire administration and secondary data were collected mainly from relevant textbooks official documents and academic journals The findings revealed that there exists a significant positive linear relationship between entrepreneurship intentions and higher educational institutions t 97 8 p 0 05 Also it was found out that 75 of the variations in socio-economic development could be attributed to the benefits of entrepreneurship in higher educational institutions r 0 753 p 0 05 The paper concluded that entrepreneurship benefits in higher educational institutions have significant implication on socio-economic development in Nigeria as it translates to the economic opportunity eradicating poverty and unemployment among graduate students in the higher educational institutions in Nigeria